An evaluation of the Ateneo de Manila University archives a user study - Gapan, Andrea Denise S.; Lagrama, Eimee Rhea C. (Quezon City School of Library and Information Studies, University of the Philippines, 2016)
Archives have a different priority compared to libraries. Their main task is to preserve documents for access. However, there is a need to conduct user studies in order to evaluate its resources, services and facilities. Through the user's perspective, the archives can see if it satisfies their information needs.
The study focused on the Ateneo de Manila University Archives' resources, services and facilities. It aimed to evaluate the archive in order to improve and develop the institution. Survey forms from the Archival Metrics Toolkit were distributed and interviews were conducted to gather data. Findings showed that there are minimal yet significant improvements needed in the archives. Despite these, the users find the archives' resources and services beyond satisfactory. Their overall visits had been successful.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Ateneo de Manila University University Archives -- Evaluation; Archives -- Use studies